INTERAKSI SOSIAL MASYARAKAT ISLAM DAN KRISTEN DI DUSUN IV TARAB MULIA DESA TARAI BANGUN KECAMATAN TAMBANG KABUPATEN KAMPAR - Alpizar Alpizar (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2011)
The research, entitled the social interaction of Islam and Christian communities in dusun iv tarab mulia desa tarai bangun kecamatan tambang kabupaten kamparisa research field that talked about the two communities of different religious communities namely Muslims and Christian communities. Although they are different religions, but they still happen interactions are woven fine. It can be applied in the form of positive communication that can be seen in the activities of mutual cooperation, patrolling, attending between the two communities, as well as mutual assistance in getting disaster. A factor driving the occurrence of social interaction is dominated by ethnic similarities that exist; it is certainly the main driver on the substance because of cultural similarities that exist.